Assessment of the 2009 fertilizer voucher program in Kano and Taraba, Nigeria - Liverpool-Tasie, Lenis Saweda; Banful, Afua Branoah; Olaniyan, Babatunde (International Food Policy Research Institute, 2010)
Despite many efforts to ease Nigerian farmers' access to quality and affordable fertilizer, it remains a key challenge for Nigerian agricultural policymakers As a result, the Nigerian government is experimenting with implementing a fertilizer voucher scheme, which is intended to improve on the current fertilizer distribution system. This brief analyzes the application of input vouchers in the Nigerian states of Kano and Taraba in 2009. It explores the effect of the voucher program on the quantity and quality of fertilizer received; the timeliness of receipt, and the price paid by respondents.